The current research status and strategies employed to modify food-derived bioactive peptides - Majura, Julieth Joram; Cao, Wenhong; Chen, Zhongqin; Htwe, Kyi Kyi; Li, Wan; Du, Ran; Zhang, Pei; Zheng, Huina; Gao, Jialong (Frontiers in Nutrition, 2022)
The ability of bioactive peptides to exert biological functions has mainly contributed to their exploitation. The exploitation and utilization of these peptides have grown tremendously over the past two decades. Food-derived peptides from sources such as plant, animal, and marine proteins and their byproducts constitute a more significant portion of the naturally-occurring peptides that have been documented. Due to their high specificity and biocompatibility, these peptides serve as a suitable alternative to pharmacological drugs for treating non-communicable diseases (such as cardiovascular diseases, obesity, and cancer). They are helpful as food preservatives, ingredients in functional foods, and dietary supplements in the food sector. Despite their unique features, the application of these peptides in the clinical and food sector is to some extent hindered by their inherent drawbacks such as toxicity, bitterness, instability, and susceptibility to enzymatic degradation in the gastrointestinal tract. Several strategies have been employed to eliminate or reduce the disadvantages of peptides, thus enhancing the peptide bioactivity and broadening the opportunities for their applications. This review article focuses on the current research status of various bioactive peptides and the strategies that have been implemented to overcome their disadvantages. It will also highlight future perspectives regarding the possible improvements to be made for the development of bioactive peptides with practical uses and their commercialization.